PTH-016 Defecating Scintigraphic Photography at St George'S Hospital: Review of Findings and Correlation with Patient Symptoms. (4th June 2013) - Rusu, R I; Beharry, N; Irwin, A; Heenan, S; Poullis, A
Abstract : Introduction: Defecating scintigraphic proctograms (DSPs) have an established position in the investigation of evacuatory problems and ano-rectal symptoms. Functional radionuclide imaging allows for both the assessment of rectoceles and correlation with evacuatory function. Methods: 151 consecutive DSPs carried out over a 3-year period were reviewed. Clinical details of presenting symptoms were reviewed with the study results. All studies were reviewed for evidence of anatomical abnormalities and function via % excretion. The % excretion was analysed in those with and without a rectocele and compared with symptoms (constipation, incontinence, rectal pain and evacuatory difficulty). The mean % excretion for each symptom (present/absent) was calculated and compared with a t test. Results: Of the 151 patients, 23 were unable to defecate and no results were available. There were 8 males, 143 females. Mean age range 55 +/- 14. 76% had a rectocele demonstrated. In all patients % excretion was significantly different in those with symptomatic evacuatory difficulty (% excretion: Constipation present/absent 63% v 62.6% p = 0.9, Incontinence present/absent 60.9% v 63.4% p = 0.46, Pain present/absent 67.2% v 62.1%, p = 0.24, Evacuatory difficulty present/absent 60.2% v 66.3% p = 0.03). Of those with a rectocele there was a non-significant trend to abnormality on excretory function (% excretion: Constipation present/absent 62.8% v 61.8% p = 0.8, Incontinence present/absent 60.9% v 62.6% p = 0.6, Pain present/absent 66.6% v 61.5%, p = 0.33, Evacuatory difficulty present/absent 59.7% v 65.9% p = 0.06). On those without a rectocele, there was no difference in excretory function in any symptom groups. Conclusion: In this large series DSPs identified rectoceles in 76% of studies. In those with a rectocele functional impairment was often present, with a trend to reduced % excretion seen. In those without a rectocele % excretion on DSPs did not differ in any symptom group. Larger reviews are needed to identify small sub-groups who may benefit from this study. The significant number with abnormalities found on DSPs suggests that this investigation may be underutilised in those with ano-rectal symptoms. Disclosure of Interest: None Declared.